2016
DOI: 10.1007/s00280-016-3060-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CYP3A5 polymorphism on the pharmacokinetics of a once-daily modified-release tacrolimus formulation and acute kidney injury in hematopoietic stem cell transplantation

Abstract: BackgroundTacrolimus is metabolized by cytochrome P450 (CYP) 3A4 and 3A5. We investigated the influence of CYP3A5 polymorphism and concurrent use of azole antifungal agents (AZ) on the pharmacokinetics of a once-daily modified-release tacrolimus formulation (Tac-QD) in patients after hematopoietic stem cell transplantation (HSCT).Design and methodsTwenty-four patients receiving allogeneic HSCT were enrolled. Genotyping for CYP3A5*3 was done by a PCR-restriction fragment length polymorphism method. Trough blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Khaled et al [20] reported that eight recipients with CYP3A5*1/*1 exhibited a significantly higher cumulative rate of grade 2–4 acute GVHD than recipients with CYP3A5*1/*3 ( n = 40) and CYP3A5*3/*3 ( n = 122) within 100 days after HSCT. Yamashita et al [21] reported that recipients with the CYP3A5*1 allele ( n = 11) exhibited a significantly higher cumulative rate of grade 3–4 acute GVHD than those with CYP3A5*3/*3 ( n = 13) within 100 days after HSCT. In this study, although there were three CYP3A5*1/*1 recipients (data not shown), grade 3–4 acute GVHD occurred in only two recipients (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khaled et al [20] reported that eight recipients with CYP3A5*1/*1 exhibited a significantly higher cumulative rate of grade 2–4 acute GVHD than recipients with CYP3A5*1/*3 ( n = 40) and CYP3A5*3/*3 ( n = 122) within 100 days after HSCT. Yamashita et al [21] reported that recipients with the CYP3A5*1 allele ( n = 11) exhibited a significantly higher cumulative rate of grade 3–4 acute GVHD than those with CYP3A5*3/*3 ( n = 13) within 100 days after HSCT. In this study, although there were three CYP3A5*1/*1 recipients (data not shown), grade 3–4 acute GVHD occurred in only two recipients (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous reports on organ transplant recipients show a significant effect of CYP3A5*3 on the pharmacokinetics of tacrolimus [17]. In HSCT recipients, several studies have shown that the concentration/dose (C/D) ratio or trough-blood concentration of tacrolimus is higher in recipients with the CYP3A5*3/*3 genotype than in those with the CYP3A5*1 allele ( *1/*1 and *1/*3 genotypes) and that the required daily dosage of tacrolimus is, thus, significantly reduced [18,19,20,21]. However, reports discussing the utility of information related to CYP3A5 polymorphism at the time of continuous intravenous infusion [18,19,20] and oral administration [21] are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Tacrolimus is metabolized by CYP3A4 and CYP3A5 and is a substrate of the drug transporter P‐glycoprotein . Patients carrying at least one functional CYP3A5 allele (CYP3A5*1) require approximately twofold higher oral tacrolimus doses than patients homozygous for CYP3A5*3 and appear to be less susceptible to drug–drug interactions with azole antimycotics, which may be explained by stronger inhibition of CYP3A4 than CYP3A5 by azoles . High expression of intestinal ABCB1 messengerRNA (mRNA) (which is translated into P‐glycoprotein) was related to higher dose requirements, but several common ABCB1 polymorphisms were not related to tacrolimus pharmacokinetics, suggesting that P‐glycoprotein is of lesser importance in oral tacrolimus pharmacokinetics.…”
mentioning
confidence: 99%
“…In fact, it has been reported that the blood concentration of tacrolimus (Tac-MR) after co-administration of FLCZ is significantly higher in CYP3A5 non-expressing patients than in those expressing CYP3A5. 19 These findings suggest that the variation in (C iv /D iv )/(C po3-5 /D po3-5 ) ratio in the FLCZ group may be attributable to the isoform selectivity of FLCZ-mediated CYP3A inhibition and interindividual differences in CYP3A5 expression. No such variation was observed in the (C iv /D iv )/ (C po1-2 /D po1-2 ) ratio.…”
Section: Ta B L E 1 Baseline Demographic Characteristics Of Hsct Patimentioning
confidence: 82%
“…When these patients take FLCZ together with tacrolimus, the potent inhibition of tacrolimus metabolism by FLCZ would occur due to lack of CYP3A5‐mediated tacrolimus metabolism. In fact, it has been reported that the blood concentration of tacrolimus (Tac‐MR) after co‐administration of FLCZ is significantly higher in CYP3A5 non‐expressing patients than in those expressing CYP3A5 . These findings suggest that the variation in ( C iv / D iv )/( C po3‐5 / D po3‐5 ) ratio in the FLCZ group may be attributable to the isoform selectivity of FLCZ‐mediated CYP3A inhibition and interindividual differences in CYP3A5 expression.…”
Section: Discussionmentioning
confidence: 98%